Does School Integration Generate Peer Effects? Evidence from Boston's Metco Program - Angrist, Joshua D; Lang, Kevin (American Economic Review, 2004)
The Metropolitan Council for Educational Opportunity (Metco) is a desegregation program that sends students from Boston schools to more affluent suburbs. Metco increases the number of blacks and reduces test scores in receiving districts. School-level data for Massachusetts and micro data from a large district show no impact of Metco on the scores of white non-Metco students. But the micro estimates show some evidence of an effect on minority third graders, especially girls. Instrumental variables estimates for third graders are imprecise but generally in line with ordinary least squares estimates. Given the localized nature of these results, we conclude that peer effects from Metco are modest and short lived.